A Perception-Based Method for the Noise Control of Construction Machines - CARLETTI, Eleonora (Archives of Acoustics, 2013)
During operation, construction machines generate high noise levels which can adversely affect the health and the job performance of operators. The noise control techniques currently applied to reduce the noise transmitted into the operator cab are all based on the decrease of the sound pressure level. Merely reducing this noise parameter may be suitable for the compliance with the legislative requirements but, unfortunately, it is not sufficient to improve the subjective human response to noise. The absolute necessity to guarantee comfortable and safe conditions for workers, requires a change of perspective and the identification of different noise control criteria able to combine the reduction of noise levels with that of psychophysical descriptors representing those noise attributes related to the subjective acoustical discomfort. This paper presents the results of a study concerning the “customization” of a methodology based on Sound Quality for the noise control of construction machines. The purpose is to define new hearing-related criteria for the noise control able to guarantee not only reduced noise levels at the operator position but also a reduced annoyance perception.